2016
DOI: 10.1155/2016/8254942
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mitochondrial Reactive Oxygen Species in Cardiovascular Injury and Protective Strategies

Abstract: Ischaemia/reperfusion (I/R) injury of the heart represents a major health burden mainly associated with acute coronary syndromes. While timely coronary reperfusion has become the established routine therapy in patients with ST-elevation myocardial infarction, the restoration of blood flow into the previously ischaemic area is always accompanied by myocardial injury. The central mechanism involved in this phenomenon is represented by the excessive generation of reactive oxygen species (ROS). Besides their harmf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 258 publications
(222 reference statements)
1
73
0
Order By: Relevance
“…However, under pathological conditions, dysfunctional uncoupled eNOS no longer produces NO, but O 2 •− , which aggravates oxidative stress (Forstermann and Sessa, ; Li and Forstermann, ). Besides enzymic sources of ROS, the mitochondrial respiratory electron transport chain (ETC), which is another important source of harmful ROS, serves as a key generator in atherosclerosis and heart diseases (Li et al, ; Muntean et al, ). Mitochondria are responsible for utilizing oxygen for energy production and oxidative phosphorylation.…”
Section: Rosmentioning
confidence: 99%
“…However, under pathological conditions, dysfunctional uncoupled eNOS no longer produces NO, but O 2 •− , which aggravates oxidative stress (Forstermann and Sessa, ; Li and Forstermann, ). Besides enzymic sources of ROS, the mitochondrial respiratory electron transport chain (ETC), which is another important source of harmful ROS, serves as a key generator in atherosclerosis and heart diseases (Li et al, ; Muntean et al, ). Mitochondria are responsible for utilizing oxygen for energy production and oxidative phosphorylation.…”
Section: Rosmentioning
confidence: 99%
“…It is well established that increased reactive oxygen species (ROS) and subsequent oxidative stress are one of the major causes of myocardial I/R injury, whereas a potential source of ROS generation is thought to be the mitochondrial respiratory chain . It has now been recognized that mitochondrial complex I is a main site of ROS production in mitochondria . Experimental evidence has shown that impairment of mitochondrial complex I activity by I/R increases the electron leakage by blocking the electron transfer at complex I and leads to ROS overproduction that ultimately induces a vicious cycle of oxidative stress .…”
Section: Introductionmentioning
confidence: 99%
“…Increases in cellular Ca 2+ and reactive oxygen species (ROS) induced by ischemia and then, amplified upon reperfusion are the main mediators of reperfusion injury [2]. Mitochondria have emerged as the major source of ROS as well as a critical target for cardioprotective strategies at reperfusion [3]. Mitochondrial Ca 2+ overload accompanied by oxidative stress and increased Pi levels leads to mitochondrial permeability transition (PT) accompanied by opening non-selective PT pores (PTP) in the inner mitochondrial membrane.…”
Section: Introductionmentioning
confidence: 99%